ENDOBILIARY INTERVENTIONS AT ACUTE NECROTIC PANCREATITIS - G. V. Rodoman (Scientific Сentre for Family Health and Human Reproduction Problems, 2014)
The study included patients with acute necrotic pancreatitis and confirmed biliary hypertension. The endoscopic retrograde cholangiopancreatography (ERSP) and endoscopic papillosphincterotomy (EPST) supplemented with lithoextrac- tion were conducted immediately. We concluded that in cases when intraduct pathology causes biliary hypertension and initial severity of patient's condition doesn't exceed 11 physiological status severity (PSS) scale conducting ERSP with EPST and lithoextraction is more preferable than drainage of gall bladder.